Nomadism of public space dwellers in Metro Manila: On their home, mobility, and survival - John XXV Paragas Lambino (Cogent Social Sciences)
The paper focuses on the contemporary urban nomadism of public space dwelling in a developing country. In particular, the paper considers the case of public space dwelling in Metro Manila which reportedly has the largest public space dweller population among the world’s metropolises. It examines their shift from sedentary living, and how they navigate the terrain of conflicts and compromises that come with the localized articulation of various modes of economic production. To probe into their characteristics, the paper employs a framework based on the heterogeneity of anthropolocal functions—i.e. how people use local spaces for economic production and human regeneration. The paper reveals that the circumstances underlying the shift to nomadic living are: unresolved land problems in the provinces that go back to the feudal era, vulnerability of local communities against natural disasters due to development unevenness between Metro Manila and the provinces, and deteriorating work conditions under a globalizing economy. The paper further identifies the living stereotype of public space dwellers as forager stereotype in which the individual band-members move relative to the mobile base camp. Lastly, the paper points out that the lives of public space dwellers in the capitalist urban environment are unstable and precarious. As a survival strategy, public space dwellers employ—albeit often unconsciously—subsistence from their urban habitat, living in small and non-hierarchical units, building social relationships that transcend consanguineous relationships, sharing of limited resource, reciprocity, and mutual aid within and outside the band, division of labour, and giving and receiving care.